Discerning the ancestry of European Americans in genetic association studies. - Price, A; Butler, J; Patterson, N; Capelli, C; Pascali, V; Scarnicci, F; Ruiz-Linares, A; Groop, L; Saetta, A; Korkolopoulou, P; Seligsohn, U; Waliszewska, A; et al. (2008)
European Americans are often treated as a homogeneous group, but in fact form a structured population due to historical immigration of diverse source populations. Discerning the ancestry of European Americans genotyped in association studies is important in order to prevent false-positive or false-negative associations due to population stratification and to identify genetic variants whose contribution to disease risk differs across European ancestries. Here, we investigate empirical patterns of population structure in European Americans, analyzing 4,198 samples from four genome-wide association studies to show that components roughly corresponding to northwest European, southeast European, and Ashkenazi Jewish ancestry are the main sources of European American population structure. Building on this insight, we constructed a panel of 300 validated markers that are highly informative for distinguishing these ancestries. We demonstrate that this panel of markers can be used to correct for stratification in association studies that do not generate dense genotype data.